Modelling economic wellbeing and social wellbeing for sustainability: a theoretical concept - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor; Mohamed, Mohd Zin (Elsevier, 2015)
The purpose of this paper is to explore relation between wellbeing and sustainability in an attempt to establish theoretical concept for sustainable wellbeing. Over the years, growing number of researches seek to understand and reason with factors that influence and constitute wellbeing and its potential synergy with sustainability. Recent studies have highlighted that factors constituting wellbeing do not necessarily indicate sustainability. Despite sustainability, studies share the same aim that is to improve wellbeing. The distinction between sustainability and wellbeing is clear. Sustainability is more of a future-oriented concept, while wellbeing accounts for present condition. Consequently, wellbeing indicators fail to capture issues, such as inequalities, climate change, scarcity of natural resources and many others. Malaysia Wellbeing Report 2014 established 14 components of wellbeing that constituted under economic and social wellbeing. In Malaysia Wellbeing Report 2014, environment and family institutions indexes correlated negatively with national economic growth. Social participation, public safety and health indexes also had weak positive correlation with the national economic growth. Two important components in sustainability are awareness and participation. Ethical and moral knowledge, as well as environmental responsibilities, are among obligations owed to as far as distant strangers at a distant time and space. Thus, sustainable wellbeing encompasses interconnectedness with people and interconnectedness with nature. Therefore, the discovery of synergy between wellbeing and sustainability involve not only measuring human capital but also the contribution of their conscious decisions to the wellbeing of the future. The paper summarized how reconciling wellbeing and sustainability unlocks opportunities for better and all-inclusive indicators for sustainable wellbeing.